Saturday

April 19, 2014

April 19, 2014

Posted by **adil** on Tuesday, December 1, 2009 at 6:00pm.

(2cosx+1)(2cosx-1)= 1 +2cos2x

- trig -
**MathMate**, Tuesday, December 1, 2009 at 6:39pmUsing

cos(2x)=cos²(x)-sin²(x)

and cos²(x)=1-sin²(x)

expand the right-hand-side to

4cos²(x)-1

which easily factorizes to the left-hand-side, namely:

(2cosx+1)(2cosx-1)

**Related Questions**

Math - Solving for Trig Equations - For the following equation, why cannot I not...

Calculus - Determine the concavity and find the points of inflection. y=2cosx + ...

Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...

Math - Find the limit of (2cosx+3cosx-2)/(2cosx-1)as x tends to pi/3.

trig - Prove the identity sin(3 pi /2 + x) + sin(3pi/2 -x) = -2cosx

Pre Calculus - Having trouble verifying this identity... cscxtanx + secx= 2cosx ...

math - tanx+secx=2cosx (sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx ...

Precalc - Prove: sin2x*sinx/2cosx + cos^2 0 = 1

trig - how do you graph the equation y=-2cosx?

Trig - cos2x(2cosx+1)=0 Solve for x.